PROSTATIC MESENCHYMAL TUMOR IN YOUNG ADULT: A CASE REPORT - Wira Amaz Gahari; Aristo (Medika Alkhairaat: Jurnal Penelitian Kedokteran dan Kesehatan, 2024)
Neoplasm in the mesenchymal tissue is only about 0.1% of the total tumors that occur in the prostate and potent to be malignant. Prostate stromal sarcoma (PSS) mostly have poor prognosis, about 50% will die within 2 years or even shorter. Here, we report a 46-years old male presented with LUTS and progressed to be urinary retention in 2 weeks. The examination results did not suggest malignancy. Digital rectal examination (DRE) showed an enlarged prostate with soft consistency and regular surface. Transabdominal ultrasonography examination showed homogeneous prostate echostructure with a volume of 80ml3, and total prostate spesific antigen (PSA) is 0.57 ng/mL. The patient then underwent transurethral resection of postate (TURP), apparently the histopathologic interpretation showed a prostate mesenchymal tumor. These tumors are divided into Stromal Tumor of Uncertain Malignant Potential (STUMP) and PSS, which should be common in 7th decade. The patient was found to have a mesenchymal tumor incidentally from prostate resection tissue. After that, an abdominal CT-Scan with contrast was performed to determine the possibility of metastasis. The patient was adviced to monitor the growth and spread of the tumor. Mesenchymal tumors are still a rare case, because the small number of similar cases reported due to very small tissues size, difficulty in distinguishing stromal neoplasms, and limited expertise of pathologists in interpreting, so we need more cases series to consider the standard therapy.